Classification of natural specializations by priority component of the telescopic model of the natural cycle of activity - Ishkov, Aleksandr (Edelweiss Applied Science and Technology, 2025)
The article considers the classification of natural specializations according to the priority components of the telescopic model of the natural cycle of activity. The model reflects the structural organization of the human nervous system. The main purpose of the research was to develop a classification of natural specializations of people based on a telescopic model. The classification is structured as a hierarchical system with three levels of detail. The first, classical level classification, corresponding to the small telescopic model, identifies four natural specializations. The second, basic classification level increases the number of natural specializations from four classical to eight basics. This is due to the allocation of two subtypes (basic specializations) in each classical specialization: concrete (right-hemisphere) and abstract (left-hemisphere). The third, detailed level of specialization increases the number of natural specializations from eight basic to sixteen detailed ones. This is due to the allocation of two subtypes (detailed specializations) in each basic specialization, reflecting the orientation to the input (afference) or output (efference) of the non-priority pole of the "interocept or exterocept" dichotomy. The classification of natural specializations highlights the initial (natural, neurophysiological) characteristics of people, which will improve the accuracy of predictions of their behavior.